1985
DOI: 10.1073/pnas.82.24.8493
|View full text |Cite
|
Sign up to set email alerts
|

Multistep transformation by defined fragments of herpes simplex virus type 2 DNA: oncogenic region and its gene product.

Abstract: ("immortalization"). However, the cells remained nontumorigenic, thereby raising obvious questions pertaining to the biological effect of the right-hand side ofBgl II C, which is now represented by the cloned BamHI E fragment (pGH17a, 0.533-0.584 m.u., Fig. 1).The present study was designed to (i) determine whether Bgl II C-induced neoplastic transformation of normal diploid SHE cells is a multistep process and (it) identify the sequences that impart tumorigenic potential. The data indicate that a 4.4-kilobase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
1

Year Published

1987
1987
1997
1997

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 29 publications
0
47
0
1
Order By: Relevance
“…Clear evidence that transformation by HSV leads to oncogenically transformed cells is not in dispute (Galloway & McDougall, 1983;Cameron et al, 1985;Hayashi et al, 1985;. Two facts arising from morphological transformation studies with HSV-2 are also generally accepted.…”
Section: Morphological Transformation Of Cultured Cells Transformamentioning
confidence: 95%
See 3 more Smart Citations
“…Clear evidence that transformation by HSV leads to oncogenically transformed cells is not in dispute (Galloway & McDougall, 1983;Cameron et al, 1985;Hayashi et al, 1985;. Two facts arising from morphological transformation studies with HSV-2 are also generally accepted.…”
Section: Morphological Transformation Of Cultured Cells Transformamentioning
confidence: 95%
“…As a result tsD can produce some early polypeptides at non-permissive temperature in addition to the IE ones. Both tsK and tsD induce the large subunit of RR but its transforming function has been associated only with established cells Hayashi et al, 1985). Macnab (1974Macnab ( , 1975Macnab ( , 1979 and Cameron et al (1985) used primary cells, and therefore the large subunit of RR is not likely to be the transforming function.…”
Section: Role Of Ribonucleotide Reductasementioning
confidence: 99%
See 2 more Smart Citations
“…1). DNA sequences from BamHI-E and its transforming subclones overlap with the coding region of the ribonucleotide reductase (RR) large subunit (RR1) and induce the tumorigenic conversion of immortalized Rat2 and Syrian hamster cell lines (1)(2)(3). Molecular analysis of the BamHI-E region showed that small DNA subfragments, mapping within the N-terminal region of RR1 ( Fig.…”
mentioning
confidence: 99%